A Family of High Step-Up Soft-Switching Integrated Sepic Converter With Y-Source Coupled Inductor - Liang Chen; Desheng Rong; Xuanjin Sun (IEEE Access, 2023)
This paper proposes a single-switch integrated Sepic converter with a Y-source coupled inductor that can be applied to the output of photovoltaic (PV) arrays. The three-winding coupled inductor has higher voltage regulation efficiency, and the three-port tap of the y-source is easier to integrate with other structures to form a composite power cell. The proposed topology gives a new type of Y-source voltage multiplication cell. While ensuring the continuous input current, it can flexibly adjust the voltage gain, increase the power capacity, and reduce the voltage stress of the switch. The diode-capacitor branch in the integrated topology is used as a clamp to suppress the voltage shock while using the absorbed leakage energy to achieve soft-switching characteristics, mitigate diode reverse recovery, and improve the efficiency of the converter. A detailed theoretical analysis of the converter is carried out, and the general extension of the topology and the extension of the converter family are given. Finally, a 150 W prototype was built to verify that the converter can achieve high gain under high efficiency of 94.3%.